Extensive preoperative workup in diffuse esophageal leiomyomatosis associated with Alport syndrome influences surgical treatment: A case report. (2015) - Dagbert, F.; Pelascini, E.; Pasquer, A.; Gincul, R.; Mion, F.; Poncet, G.; Robert, M.
Highlights: Diffuse esophageal leiomyomatosis is frequently associated with Alport syndrome. Only curative option is esophagectomy. Misdiagnosis is common and workup should include endoscopic ultrasonography and 3D-gastric computed tomography for better anatomical delineation. Extensive imaging workup can result in better operative planning. Total esophagectomy should include all diseased tissue and provide good long term quality of life. Abstract: Introduction: Diffuse esophageal leiomyomatosis is a rare disease. Misdiagnosis is frequent and previous surgeries can complicate surgical management. The only treatment described for severe symptomatic cases is esophagectomy. Presentation of case: We describe a case of diffuse esophageal leiomyomatosis associated with Alport syndrome in a 21 year-old female where endoscopic ultrasonography (EUS) with concomitant fluoroscopy and 3D-gastric computed tomography (3D-GCT) modified surgical management. Discussion: The diagnosis of diffuse esophageal leiomyomatosis is difficult but can be greatly facilitated by extensive endoscopic and radiologic workup. Esophagectomy should only be entertained after complete anatomic mapping of the lesions, especially after previous surgeries. Conclusion: EUS and 3D-GCT should strongly be considered as part of routine preoperative workup in these patients.